1972
DOI: 10.1021/jf60179a029
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate degrading enzymes in the crude supernatant fraction from the rat liver

Abstract: Attempts were made to classify the enzymes which degrade insecticidal organophosphates in the crude supernatant fraction (i.e. 20,000 X g supernatant) of the rat liver. On the basis of cofactor and ion activation characteristics of the enzymes, four distinctly different types of enzymes have been observed. The enzymes which degraded malathion and parathion were detected by the electrophoresis method. Electrophoresis treatments did not, however, facilitate the detection of Ca2+ or GSHstimulated enzymes. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Many toxic OPs as diazinon containing a sulfur atom undergo oxidation to oxons [17]- [22], and their biotransformation yields substances with increased toxicity. Parathion has an analogous ability to be oxidized to paraoxon and yield more toxic oxons [23]- [25] (Scheme 2). The reactions of transformation and biotransformation of phosphorothioates to the corresponding (more toxic) oxons are common among all members of this family of substances, and can be supported by examples of important phosphorothioates: salithion [26] and cyanox [27].…”
Section: Toxicity Of Opsmentioning
confidence: 99%
“…Many toxic OPs as diazinon containing a sulfur atom undergo oxidation to oxons [17]- [22], and their biotransformation yields substances with increased toxicity. Parathion has an analogous ability to be oxidized to paraoxon and yield more toxic oxons [23]- [25] (Scheme 2). The reactions of transformation and biotransformation of phosphorothioates to the corresponding (more toxic) oxons are common among all members of this family of substances, and can be supported by examples of important phosphorothioates: salithion [26] and cyanox [27].…”
Section: Toxicity Of Opsmentioning
confidence: 99%
“…Some investigators have shown that bacterial enzymes cause degradations of several organophosphorothioates such as malathion (Lai et al, 1998). Although many cases of enzymatic degradation of organophosphorus pesticides by mammal (Menn et al, 1996;Miyata and Matsumura, 1972) or insect (Severini et al, 1997;Campbell et al, 1997;Wood et al, 1986;Wool et al, 1982) enzymes have been studied, those by plant enzyme have not been as extensively studied (Bedi and Roy, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…gated (Appleton and Nakatsugawa, 1977;Fuhremann et al, 1974;Gaines et al, 1966;Ku and Dahm, 1973;Lichtenstein et al, 1973;Miyata and Matsumura, 1972;Nakatsugawa and Dahm, 1967;Nakatsugawa et al, 1968Nakatsugawa et al, , 1969Neal, 1967a,b;Neal and DuBois, 1965;Pankaskie et al, 1952;Whitehouse and Ecobichon, 1975) and reviewed (Schoenig, 1975). These studies have revealed an ^ vivo metabolic manipulation of parathion via two pathways (Figure 1).…”
Section: Hepatic Biotransformation Mechanisms Have Been Extensively Imentioning
confidence: 99%